Measurement of Some Argon Plasma Parameters Glow Discharge Under Axial Magnetic Field - Karim, Pshtiwan M.A.; Mayi, Diyar S.; Al-Hakary, Shamo Kh. (Science Journal of University of Zakho, 2019)
This paper investigates the characteristics some of argon plasma parameters of glow discharge under axial magnetic field. The DC power supply of range (0-6000) V is used as a breakdown voltage to obtain the discharge of argon gas. The discharge voltage-current (V-I) characteristic curves and Paschen’s curves as well as the electrical conductivity were studied with the presents of magnetic field confinement at different gas pressures. The magnetic field up to 25 mT was obtained using four coils of radius 6 cm and 320 turn by passing A.C current up to 5 Amperes. Spectroscopic measurements are employed for purpose of estimating two main plasma parameters electron temperature (Te) and electron density (ne). Emission spectra from positive column (PC) zone of the discharge have been studies at different values of magnetic field and pressures at constant discharge currents of 1.5 mA. Electron temperature (Te) and its density are calculated from the ratio of the intensity of two emission lines of the same lower energy levels. Experimental results show the abnormal glow region characteristics (positive resistance). Breakdown voltage versus pressure curves near the curves of paschen and decrease as magnetic field increases due to magnetic field confinement of plasma charged particles. Also the electrical conductivity increases due to enhancing magnetic field at different gas pressures. Both temperature density of electron and the intensities of two selected emission lines decrease with increasing pressure due decreasing of mean free path of electron. Electron density increase according to enhancing magnetic field, while the intensity of emitting lines tends to decrease.